Semiotics and education in the Human Sciences: Notes on theories and methods of semiotics in educational research (Encuentros, 2020)
The author considers this book as the result of his academic and research work, compiled from the notes and work materials of the semiotics seminars during his studies in the Doctorate in Human Sciences, which has been enriched with contributions from professors, his teaching experience and the work carried out by the author in the Laboratory of Semiotic and Anthropological Research; through the investigations carried out in Venezuela, Costa Rica, Chile and Argentina, which is expected to continue.keywords: Semiotics, education, methodology, Humans Sciences, research.